Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Discover reliable solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

A mistake was made in the steps shown to simplify the expression. Which step includes the mistake?

[tex]\[ \frac{9}{2} + 3(4-1) - 7 + 2^3 \][/tex]

Step 1: [tex]\[ = \frac{9}{2} + 3(3) - 7 + 2^3 \][/tex]
Step 2: [tex]\[ = \frac{9}{2} + 3(3) - 7 + 8 \][/tex]
Step 3: [tex]\[ = \frac{15}{2} + 3(3) - 7 + 8 \][/tex]
Step 4: [tex]\[ = \frac{45}{2} - 7 + 8 \][/tex]
Step 5: [tex]\[ = \frac{31}{2} + 8 \][/tex]
Step 6: [tex]\[ = \frac{47}{2} \][/tex]

A. Step 4
B. Step 1
C. Step 3


Sagot :

To identify which step contains the mistake in the given expression simplification, let’s go through the steps one by one.

The original expression is:
[tex]\[ \frac{9}{2} + 3(4-1) - 7 + 2^3 \][/tex]

Step 1: Evaluate the expression inside the parentheses (4-1) and the power [tex]\( 2^3 \)[/tex]:
[tex]\[ = \frac{9}{2} + 3(3) - 7 + 8 \][/tex]
Step 1 is correct.

Step 2: Perform the multiplication [tex]\(3(3)\)[/tex] and keep evaluating [tex]\(2^3 = 8\)[/tex]:
[tex]\[ = \frac{9}{2} + 9 - 7 + 8 \][/tex]
Step 2 is correct.

Step 3: Here, we need to check the correctness. At this step, we should just continue adding and subtracting left to right:
The given Step 3 is:
[tex]\[ = \frac{15}{2} (3) - 7 + 8 \][/tex]
This is incorrect because the [tex]\(\frac{9}{2}\)[/tex] should not be multiplied by 3. Instead, we should sum and subtract the terms as they are:

Let's correct this step:
[tex]\[ = \frac{9}{2} + 9 - 7 + 8 \][/tex]

Step 4: Combine the terms left to right correctly:
For correct calculation:
[tex]\[ \frac{9}{2} = 4.5 \implies 4.5 + 9 - 7 + 8 \][/tex]
[tex]\[ = 4.5 + 9 = 13.5\][/tex]
\]
[tex]\[ = 13.5 - 7 = 6.5 \][/tex]
[tex]\[ = 6.5 + 8 = 14.5 \][/tex]

Our correct result should be [tex]\(\frac{29}{2} (= 14.5)\)[/tex]. But in the given incorrect simplification:
\[
= \frac{45}{2} - 7 + 8
This implies \[ Step 3. Step 3 should not include multiplication

So, the mistake is in Step 3.

The correct expression without mistakes is:
\(\result {29}{2}\}.

Therefore, the correct answer choice is:
C. Step 3
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.